Epoxy resin composition, adhesive, cured product and molding material

JP7639414B2Active Publication Date: 2025-03-05MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021038748
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-10
Publication Date
2025-03-05
Estimated Expiration
2041-03-10

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、接着強度に優れる硬化物が得られるエポキシ樹脂組成物とその硬化物、接着剤及び成形材料を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639414000010
    Figure 0007639414000010
  • Figure 0007639414000011
    Figure 0007639414000011
  • Figure 0007639414000001
    Figure 0007639414000001
Patent Text Reader

Abstract

To provide an epoxy resin composition from which a cured product excellent in adhesive strength can be obtained and a cured product of the same, an adhesive and a molding material.SOLUTION: An epoxy resin composition contains a (meth)acrylic polymer (A), a polymer (B) having a core-shell structure, an epoxy resin (C) and a curing agent (D), wherein the (meth)acrylic polymer (A) has a structural unit derived from a vinyl radical polymerizable monomer (a1) and a structural unit derived from a macro monomer (a2), and the polymer (B) having the core-shell structure contains a polymer (b1) having a core-shell structure having a particle diameter of 50-190 nm, and a polymer (b2) having a core-shell structure having a particle diameter of 195-300 nm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin composition, an adhesive, a cured product, and a molding material. [Background technology]

[0002] Epoxy resins have excellent rigidity, heat resistance, electrical properties, durability, etc., and are therefore used in vehicle structural adhesives, civil engineering and construction adhesives, adhesives for electronic materials, industrial adhesives, etc. On the other hand, epoxy resins are brittle and have poor impact resistance and adhesive strength. Therefore, studies are being conducted to impart toughness to epoxy resins by blending them with thermoplastic acrylic resins or polymers with a core-shell structure.

[0003] For example, Patent Document 1 discloses that a cured product having excellent adhesive strength can be obtained from an epoxy resin composition containing an epoxy resin and a (meth)acrylic polymer having a structural unit derived from a macromonomer. Furthermore, Patent Document 2 discloses that a cured product excellent in toughness, impact resistance and adhesive strength can be obtained from an epoxy resin composition containing an epoxy resin, a rubber-containing polymer, and a (meth)acrylic copolymer having a structural unit derived from a macromonomer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 049951 [Patent Document 2] International Publication No. 2020 / 213642 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the cured products of the epoxy resin compositions described in Patent Documents 1 and 2 do not necessarily have satisfactory adhesive strength. An object of the present invention is to provide an epoxy resin composition which can give a cured product having excellent adhesive strength, and a cured product thereof, an adhesive, and a molding material. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] An epoxy resin composition comprising a (meth)acrylic polymer (A), a polymer having a core-shell structure (B), an epoxy resin (C) and a curing agent (D), the (meth)acrylic polymer (A) has a structural unit derived from a vinyl radically polymerizable monomer (a1) and a structural unit derived from a macromonomer (a2), The epoxy resin composition, wherein the polymer (B) having a core-shell structure contains a polymer (b1) having a core-shell structure and having a particle diameter of 50 to 190 nm, and a polymer (b2) having a core-shell structure and having a particle diameter of 195 to 300 nm. [2] The epoxy resin composition according to [1] above, wherein the number of particles of the polymer (b1) having a core-shell structure and the number of particles of the polymer (b2) having a core-shell structure satisfy the following formula (i): 0.05≦(number of particles of polymer (b1) having a core-shell structure / number of particles of polymer (b2) having a core-shell structure)≦20 (i) [3] The epoxy resin composition according to [1] or [2] above, wherein the core layer of the polymer (B) having a core-shell structure is one or more selected from the group consisting of diene-based rubber polymers, acrylic-based rubber polymers, and organosiloxane-based rubber polymers, and the shell layer of the polymer (B) having a core-shell structure is a vinyl-based polymer. [4] The epoxy resin composition according to any one of the above [1] to [3], wherein the macromonomer (a2) has a structural unit derived from a vinyl radically polymerizable monomer (a3). [5] The epoxy resin composition according to [4] above, wherein the macromonomer (a2) has a structure represented by the following general formula (1):

[0007] [ka]

[0008] In formula (1), X 1 ~X n-1 are each independently a hydrogen atom, a methyl group, or CHOH; Y 1 ~Y n each independently represents X bonded to a vinyl group of the vinyl radical polymerizable monomer (a3); 1 ~X n-1 Z is a terminal group, and n is an integer of 2 to 10,000.

[0009] [6] The epoxy resin composition according to [4] or [5] above, wherein the vinyl radical polymerizable monomer (a3) ​​contains a (meth)acrylate having a cyclic ether group. [7] An adhesive comprising the epoxy resin composition according to any one of [1] to [6] above. [8] A cured product of the epoxy resin composition according to any one of [1] to [6] above. [9] A molding material containing the cured product of [8]. Effect of the Invention

[0010] According to the present invention, it is possible to provide an epoxy resin composition which gives a cured product having excellent adhesive strength, the cured product thereof, an adhesive, and a molding material. [Brief description of the drawings]

[0011] [Figure 1] 1 is a transmission electron microscope (TEM) image of a cured resin containing a polymer (X) having a core-shell structure obtained in Production Example 22. [Diagram 2] 1 is a transmission electron microscope (TEM) image of a cured resin containing the polymer (B-1) having a core-shell structure used in Examples 1 to 25. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The following embodiments are merely examples for explaining the present invention, and are not intended to limit the present invention to these embodiments. The present invention can be implemented in various forms without departing from the spirit of the present invention. In the present invention, "(meth)acrylic" is a general term for "acrylic" and "methacrylic". "(meth)acrylate" is a general term for "acrylate" and "methacrylate". "(meth)acryloyl group" is a general term for "acryloyl group" and "methacryloyl group", and is a group represented by CH2=C(R)-C(=O)- (R is a hydrogen atom or a methyl group). "Macromonomer" means a compound having a radical polymerizable group or an addition-reactive functional group. "Vinyl radical polymerizable monomer" means a monomer having an ethylenically unsaturated bond that is not a macromonomer. In the present invention, the "cured product" refers to a cured product of the epoxy resin composition of the present invention.

[0013] [Epoxy resin composition] The epoxy resin composition of the present invention contains a (meth)acrylic polymer (A) (hereinafter also referred to as "component (A)"), a polymer (B) having a core-shell structure (hereinafter also referred to as "component (B)"), an epoxy resin (C) (hereinafter also referred to as "component (C)"), and a curing agent (D) (hereinafter also referred to as "component (D)") shown below. The epoxy resin composition of the present invention may contain components other than the components (A), (B), (C) and (D) (hereinafter also referred to as "optional components"), as necessary, to the extent that the effects of the present invention are not impaired.

[0014] <Component (A)> The component (A) is a (meth)acrylic polymer (A). The (meth)acrylic polymer (A) is a copolymer having a structural unit derived from a vinyl radically polymerizable monomer (a1) and a structural unit derived from a macromonomer (a2). The component (A) may be used alone or in combination of two or more types.

[0015] Examples of the vinyl radical polymerizable monomer (a1) include monofunctional (meth)acrylates, polyfunctional (meth)acrylates, and vinyl compounds other than monofunctional (meth)acrylates and polyfunctional (meth)acrylates (hereinafter also referred to as "other vinyl compounds"). Specific examples of monofunctional (meth)acrylates include (meth)acrylic acid, (meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxyethyl hexahydrophthalate, and other (meth)acrylates containing a carboxyl group; methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, and i-propyl (Meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, s-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate Acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, i-amyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, i-nonyl (meth)acrylate, i-decyl (meth)acrylate, 3-i-propylheptyl (meth)acrylate, i-undecyl (meth)acrylate, 2-t-butylheptyl (meth)acrylate, i-dodecyl (meth)acrylate, i-tridecyl (meth)acrylate, i-tetradecyl (Meth)acrylates having an alkyl group, such as decyl (meth)acrylate; (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerin mono(meth)acrylate, ethylene glycol mono(meth)acrylate, and propylene glycol mono(meth)acrylate;(Meth)acrylates having a cycloalkyl group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenoxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, and 1,4-cyclohexanedimethanol monoacrylate; phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, (1-naphthyl)methy (Meth)acrylates having an aryl group, such as aryl (meth)acrylate; tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (meth)acryloylmorpholine, (3,4-epoxycyclohexyl)methyl (meth)acrylate, β-methylglycidyl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ( (meth)acrylates having a cyclic ether group, such as (2-methyl-2-ethyl-1,3-dioxolan-4-yl)(meth)acrylate and (5-ethyl-1,3-dioxan-5-yl)methyl (meth)acrylate; alkoxyalkyl (meth)acrylates, such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate;Examples of the silane include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloyloxyethyl acid phosphate, trifluoroethyl (meth)acrylate and heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and (meth)acrylamide. These monofunctional (meth)acrylates may be used alone or in combination of two or more kinds.

[0016] Specific examples of polyfunctional (meth)acrylates include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, polybutylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, polycarbonate diol di(meth)acrylate, polyester diol di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A dimeth ... Examples of the functional (meth)acrylate include difunctional (meth)acrylates such as propylene oxide adduct di(meth)acrylate of terephthalic acid A, polyurethane di(meth)acrylate, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene; trifunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, and ε-caprolactone-modified tris((meth)acryloxyethyl)isocyanurate; tetrafunctional (meth)acrylates such as ditrimethylolpropane tetra(meth)acrylate; pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate; and hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate. These polyfunctional (meth)acrylates may be used alone or in combination of two or more kinds.

[0017] The other vinyl-based compound is not particularly limited as long as it is copolymerizable with the monofunctional (meth)acrylate and the polyfunctional (meth)acrylate, and examples thereof include styrene or styrene derivatives such as styrene, α-methylstyrene, pt-butylstyrene, vinyltoluene, etc.; acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, etc.; unsaturated carboxylic acids such as itaconic acid, maleic acid, fumaric acid, etc.; unsaturated nitriles such as (meth)acrylonitrile, etc.; unsaturated carboxylic acid esters such as diethyl maleate, dibutyl maleate, dibutyl fumarate, diethyl itaconate, dibutyl itaconate, etc.; and vinyl esters such as vinyl acetate, vinyl propionate, etc. These other vinyl compounds may be used alone or in combination of two or more.

[0018] As the vinyl radical polymerizable monomer (a1), from the viewpoints of low glass point transition and high effect of improving adhesive strength of the cured product, (meth)acrylates having an alkyl group are preferred, and acrylates having an alkyl group are more preferred. Among them, acrylates having an alkyl group with 1 to 22 carbon atoms are more preferred, and acrylates having an alkyl group with 1 to 14 carbon atoms are particularly preferred.

[0019] The macromonomer (a2) is not particularly limited as long as it is a compound having a radically polymerizable group or an addition-reactive functional group. From the viewpoint of high degree of design for solubility in component (C), however, a compound containing a constituent unit derived from a vinyl radically polymerizable monomer (a3) ​​is preferred, and a compound containing two or more constituent units derived from a vinyl radically polymerizable monomer (a3) ​​and having a radically polymerizable group at an end is more preferred. Examples of the vinyl radical polymerizable monomer (a3) ​​include the same as the vinyl radical polymerizable monomer (a1). Among them, in particular, from the viewpoint of high solubility in the (C) component and higher adhesive strength of the cured product, (meth)acrylates having an alkyl group and (meth)acrylates having a cyclic ether group are preferred, (meth)acrylates having an alkyl group with 1 to 22 carbon atoms and (meth)acrylates having a cyclic ether group are more preferred, methacrylates having an alkyl group with 1 to 22 carbon atoms and methacrylates having a cyclic ether group are even more preferred, and methacrylates having an alkyl group with 1 to 8 carbon atoms, glycidyl methacrylate, 4-hydroxybutyl methacrylate glycidyl ether, (3,4-epoxycyclohexyl)methyl methacrylate, and β-methylglycidyl methacrylate are particularly preferred.

[0020] The macromonomer (a2) preferably has a structure represented by the following general formula (1) in view of excellent radical polymerizability with the vinyl radically polymerizable monomer (a1).

[0021] [ka]

[0022] In formula (1), X 1 ~X n-1 are each independently a hydrogen atom, a methyl group, or CHOH; Y 1 ~Y n each independently represents X bonded to a vinyl group of the vinyl radical polymerizable monomer (a3); 1 ~X n-1 Z is a terminal group, and n is an integer of 2 to 10,000. In addition, "-···-" in formula (1) represents a state in which the monomer units are polymerized.

[0023] X 1 ~X n-1 are each independently a hydrogen atom, a methyl group, or CHOH, and a methyl group is preferred. From the viewpoint of ease of synthesis, X1 ~X n-1 It is preferable that at least half of the groups are methyl groups.

[0024] Y 1 ~Y n each independently represents X bonded to a vinyl group of the vinyl radical polymerizable monomer (a3); 1 ~X n-1 Examples of such substituents include OR 1 , halogen atom, COR 2 , COOR 3 , C.N., C.O.N. 4 R 5 , N.H.C.O.R. 6 , or R 7 In addition, R 1 ~R 7 are each independently a hydrogen atom, an alkyl group, a cycloalkyl group, a cyclic ether group, an aryl group, or a heteroaryl group. R 1 ~R 7 The alkyl group in may be linear or branched. The number of carbon atoms in the alkyl group is preferably 1 to 20. Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a t-butyl group, an i-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a 2-ethylhexyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, an octadecyl group, a nonadecyl group, and an icosyl group. Specific examples of the cycloalkyl group include a cyclopentyl group, a cyclohexyl group, an isobornyl group, a dicyclopentenyl group, a dicyclopentenoxyethyl group, a dicyclopentanyl group, an adamantyl group, and a 4-methanolcyclohexyl group. Specific examples of the cyclic ether group include a tetrahydrofurfuryl group, a glycidyl group, a (3,4-epoxycyclohexyl)methyl group, and a (3-ethyloxetan-3-yl)methyl group. Specific examples of the aryl group include a phenyl group, a benzyl group, a phenoxyethyl group, and a naphthyl group. R 1 ~R 7 The number of carbon atoms in the heteroaryl group in the formula (I) is preferably 4 to 18. Specific examples of the heteroaryl group include a pyridyl group and a carbazolyl group.

[0025] Z is a terminal group. The terminal group may be a hydrogen atom or a group derived from a radical polymerization initiator, similar to the terminal groups of polymers obtained by known radical polymerization. n represents the number of monomer units in one molecule of the macromonomer (a2), and is an integer from 2 to 10,000, preferably an integer from 5 to 1,000, and more preferably an integer from 10 to 500.

[0026] The number average molecular weight (Mn) of the macromonomer (a2) is preferably from 300 to 30000, more preferably from 500 to 20000, and further preferably from 1000 to 10000. When the number average molecular weight of the macromonomer (a2) is within the above range, the solubility in the component (C) is improved. The mass average molecular weight (Mw) of the macromonomer (a2) is preferably 500 to 100000, more preferably 1000 to 50000, and further preferably 2000 to 30000. When the mass average molecular weight of the macromonomer (a2) is within the above range, the solubility in the component (C) is improved. The Mw / Mn of the macromonomer (a2) is preferably from 1 to 5, and more preferably from 1.5 to 3. When the Mw / Mn of the macromonomer (a2) is within the above range, the solubility in the component (C) is improved. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the macromonomer (a2) are polystyrene-equivalent values ​​measured by gel permeation chromatography (GPC).

[0027] The macromonomer (a2) may be one produced by a known method, or a commercially available one. Examples of methods for producing the macromonomer (a2) include a method using a cobalt chain transfer agent (U.S. Pat. No. 4,680,352, etc.), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (WO 1988 / 04304), a method of chemically bonding a polymerizable group (JP-A-60-133007 and U.S. Pat. No. 5,147,952, etc.), and a method using thermal decomposition (JP-A-11-240854, etc.). As a method for producing the macromonomer (a2), a method using a cobalt chain transfer agent is preferred in terms of the number of production steps and the use of a catalyst with a high chain transfer constant. Since the cobalt chain transfer agent has a high chain transfer constant, a macromonomer (a2) with a controlled molecular weight can be obtained by adding a small amount of the agent.

[0028] As the cobalt chain transfer agent, a known cobalt complex can be used. The amount of the cobalt chain transfer agent used is preferably 0.00001 to 0.1 parts by mass, more preferably 0.00005 to 0.05 parts by mass, and even more preferably 0.0001 to 0.02 parts by mass, based on 100 parts by mass of the vinyl radical polymerizable monomer (a3).

[0029] When the total of the constituent units derived from the vinyl radical polymerizable monomer (a1) and the constituent units derived from the macromonomer (a2) is taken as 100 mass%, the proportion of the constituent units derived from the vinyl radical polymerizable monomer (a1) is preferably 20 to 95 mass%, more preferably 30 to 90 mass%, and even more preferably 40 to 85 mass%. The proportion of the constituent units derived from the macromonomer (a2) is preferably 5 to 80 mass%, more preferably 10 to 70 mass%, and even more preferably 15 to 60 mass%. When the proportions of the constituent units derived from the vinyl radical polymerizable monomer (a1) and the constituent units derived from the macromonomer (a2) are each within the above range, the solubility in the (C) component is improved, and the adhesive strength of the cured product is further increased. The vinyl radical polymerizable monomer (a1) and the macromonomer (a2) may each be used alone or in combination of two or more kinds.

[0030] The component (A) and the macromonomer (a2) can be produced by known methods such as solution polymerization, suspension polymerization, emulsion polymerization, and redox polymerization.

[0031] The mass average molecular weight (Mw) of the component (A) is preferably from 1,000 to 1,000,000, more preferably from 3,000 to 800,000, and even more preferably from 5,000 to 500,000. When the mass average molecular weight of the component (A) is within the above range, the solubility in the component (C) is improved. The number average molecular weight (Mn) of the component (A) is preferably from 500 to 300000, more preferably from 1000 to 100000, and even more preferably from 3000 to 50000. When the number average molecular weight of the component (A) is within the above range, the solubility in the component (C) is improved. The Mw / Mn of the component (A) is preferably from 1 to 10, and more preferably from 1.5 to 8. When the Mw / Mn of the component (A) is within the above range, the solubility in the component (C) is improved. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the component (A) are each values ​​calculated as polystyrene equivalents measured by gel permeation chromatography (GPC).

[0032] <(B) component> The component (B) is a polymer (B) having a core-shell structure. The polymer (B) having a core-shell structure contains a polymer (b1) having a core-shell structure with a particle diameter of 50 to 190 nm and a polymer (b2) having a core-shell structure with a particle diameter of 195 to 300 nm. By containing the polymer (b1) having a core-shell structure and the polymer (b2) having a core-shell structure in the polymer (B) having a core-shell structure, it is possible to increase the adhesive strength of the cured product while suppressing an excessive increase in viscosity of the epoxy resin composition. It is preferable that the number of particles of the polymer (b1) having a core-shell structure and the number of particles of the polymer (b2) having a core-shell structure satisfy the following formula (i). 0.05≦(number of particles of polymer (b1) having a core-shell structure / number of particles of polymer (b2) having a core-shell structure)≦20 (i)

[0033] When the ratio (hereinafter, also referred to as "b1 / b2 ratio") expressed by the number of particles of the polymer (b1) having a core-shell structure / the number of particles of the polymer (b2) having a core-shell structure is equal to or higher than the lower limit, the increase in viscosity of the epoxy resin composition can be further suppressed. When the b1 / b2 ratio is equal to or lower than the upper limit, the adhesive strength of the cured product is further increased. The b1 / b2 ratio is preferably from 0.1 to 15, more preferably from 1 to 10, and further preferably from 3 to 8. The b1 / b2 ratio can be measured as follows: Using image processing software, the length of the major axis of the polymer having a core-shell structure is measured as the particle diameter from a transmission electron microscope (TEM) image of a cured resin containing the polymer (B) having a core-shell structure, the number of particles of the polymer (b1) having a core-shell structure with a particle diameter of 50 to 190 nm and the number of particles of the polymer (b2) having a core-shell structure with a particle diameter of 195 to 300 nm are counted, and the ratio (b1 / b2 ratio) is calculated, which is the b1 / b2 ratio in the component (B) contained in the epoxy resin composition. The cured resin is obtained by curing a resin composition containing a polymer (B) having a core-shell structure, an epoxy resin, a curing agent, and a curing accelerator. The epoxy resin, curing agent, and curing accelerator contained in the resin composition used to measure the b1 / b2 ratio are the same as those of the component (C), component (D), and optional components described below.

[0034] The polymer (B) having a core-shell structure may contain a polymer having a core-shell structure other than the polymer (b1) having a core-shell structure and the polymer (b2) having a core-shell structure (hereinafter also referred to as "polymer (b3) having a core-shell structure"), if necessary, within a range that does not impair the effects of the present invention. In order to obtain an excellent balance between the viscosity of the epoxy resin composition and the adhesive strength of the cured product, it is preferable that the number of particles of the polymer (b1) having a core-shell structure, the number of particles of the polymer (b2) having a core-shell structure, and the number of particles of the polymer (b3) having a core-shell structure satisfy the following formula (ii). {(number of particles of polymer (b3) having a core-shell structure) / (number of particles of polymer (b1) having a core-shell structure+number of particles of polymer (b2) having a core-shell structure)}≦0.01 (ii)

[0035] The structure of the polymer (B) having a core-shell structure is preferably such that the core layer is one or more selected from the group consisting of diene-based rubber polymers, acrylic-based rubber polymers, and organosiloxane-based rubber polymers, and the shell layer is a vinyl-based polymer.

[0036] An example of the diene rubber polymer is a copolymer of 1,3-butadiene, a vinyl monomer copolymerizable therewith, and, if necessary, a crosslinkable monomer. Examples of vinyl monomers include aromatic vinyls such as styrene and α-methylstyrene, alkyl methacrylates such as methyl methacrylate and ethyl methacrylate, alkyl acrylates such as ethyl acrylate and n-butyl acrylate, unsaturated nitriles such as acrylonitrile and methacrylonitrile, vinyl ethers such as methyl vinyl ether and butyl vinyl ether, vinyl halides such as vinyl chloride and vinyl bromide, vinylidene halides such as vinylidene chloride and vinylidene bromide, and vinyl monomers having a glycidyl group such as glycidyl acrylate, glycidyl methacrylate, allyl glycidyl ether, and ethylene glycol glycidyl ether. These vinyl monomers may be used alone or in combination of two or more. Examples of the crosslinkable monomer include aromatic polyfunctional vinyl compounds such as divinylbenzene and divinyltoluene, polyfunctional (meth)acrylates such as ethylene glycol di(meth)acrylate and 1,3-butanediol di(meth)acrylate, tri(meth)acrylic acid esters, carboxylic acid allyl esters such as allyl (meth)acrylate, diallyl compounds or triallyl compounds such as diallyl phthalate, diallyl sebacate and triallyl triazine, etc. These crosslinkable monomers may be used alone or in combination of two or more.

[0037] Diene rubber polymers can usually be produced by emulsion polymerization, in which 1,3-butadiene, one or more vinyl monomers copolymerizable therewith, and optionally a crosslinkable monomer are polymerized in the presence of a polymerization initiator, an emulsifier, and optionally a chain transfer agent. Examples of the polymerization initiator include water-soluble persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate; redox initiators containing an organic peroxide as one component such as diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide; and combinations of a peroxide and one or more reducing agents. As the emulsifier, a known emulsifier can be appropriately used. Examples of the chain transfer agent include t-dodecyl mercaptan, n-octyl mercaptan, and α-methylstyrene. The polymerization temperature varies depending on the type of polymerization initiator, but is usually in the range of 40 to 80°C. As the emulsion polymerization method, a single-stage or multi-stage seed polymerization method may be used. In some cases, a soap-free polymerization method may be used. In addition, in order to adjust the particle size of the diene rubber polymer, the obtained rubber latex may be enlarged with an acid or a salt.

[0038] Examples of acrylic rubber polymers include copolymers of (meth)acrylic acid esters, vinyl monomers that can be copolymerized therewith as necessary (excluding (meth)acrylic acid esters and polyfunctional monomers), and polyfunctional monomers. Examples of the (meth)acrylic acid ester include the monofunctional (meth)acrylates exemplified above in the description of the component (A). The polyfunctional monomer serves as a cross-linking agent or a graft-linking agent. Examples of the crosslinking agent include the polyfunctional (meth)acrylates exemplified above in the description of the component (A). Examples of the graft crossing agent include allyl methacrylate, triallyl cyanurate, triallyl isocyanurate, etc. These graft crossing agents may be used alone or in combination of two or more kinds. Examples of the vinyl monomer include the other vinyl compounds exemplified above in the explanation of component (A).

[0039] The acrylic rubber polymer can be produced usually by emulsion polymerization, preferably soap-free emulsion polymerization, or, if necessary, forced emulsion polymerization. As the polymerization initiator, there may be mentioned the polymerization initiators exemplified above in the explanation of the diene rubber polymer. As an emulsifier, disproportionated rosin acid, alkali metal salts of higher fatty acids such as oleic acid and stearic acid, and alkali metal salts of sulfonic acids such as dodecylbenzenesulfonic acid may be added as necessary. In order to adjust the particle size of the acrylic rubber polymer, the resulting rubber latex may be enlarged with an acid or a salt.

[0040] The organosiloxane-based rubber polymer is preferably a polyorganosiloxane containing a vinyl polymerizable functional group. The polyorganosiloxane containing a vinyl polymerizable functional group is obtained by polymerizing dimethylsiloxane, a siloxane containing a vinyl polymerizable functional group, and, if necessary, a siloxane-based crosslinking agent. The dimethylsiloxane may be a dimethylsiloxane-based cyclic compound having 3 or more members, preferably a 3- to 7-membered ring. Specific examples include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane. These dimethylsiloxanes may be used alone or in combination of two or more. The vinyl polymerizable functional group-containing siloxane has a vinyl polymerizable functional group and can be bonded to dimethylsiloxane via a siloxane bond. In consideration of the reactivity with dimethylsiloxane, various alkoxysilane compounds having a vinyl polymerizable functional group are preferable as the vinyl polymerizable functional group-containing siloxane. Specifically, methacryloyloxysilanes such as β-methacryloyloxyethyldimethoxymethylsilane, γ-methacryloyloxypropyldimethoxymethylsilane, γ-methacryloyloxypropylmethoxydimethylsilane, γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropylethoxydiethylsilane, γ-methacryloyloxypropylethoxydiethoxymethylsilane, δ-methacryloyloxybutyldiethoxymethylsilane, etc.; vinylsiloxanes such as tetramethyltetravinylcyclotetrasiloxane, etc.; vinylphenylsilanes such as p-vinylphenyldimethoxymethylsilane, etc.; mercaptosiloxanes such as γ-mercaptopropyldimethoxymethylsilane, etc. These vinyl polymerizable functional group-containing siloxanes may be used alone or in combination of two or more. Examples of the siloxane-based crosslinking agent include trifunctional or tetrafunctional silane-based crosslinking agents, such as trimethoxymethylsilane, triethoxyphenylsilane, tetramethoxysilane, tetraethoxysilane, tetrabutoxysilane, etc. These siloxane-based crosslinking agents may be used alone or in combination of two or more.

[0041] The polyorganosiloxane can be produced, for example, as follows. First, the siloxane mixture containing dimethylsiloxane, vinyl polymerizable functional group-containing siloxane, and optionally siloxane-based crosslinking agent is emulsified with emulsifier and water to prepare latex.Then, the obtained latex is pulverized by using a homomixer that pulverizes by the shearing force of high speed rotation, a homogenizer that pulverizes by the jetting force of high pressure generator, etc., and then polymerized under high temperature using acid catalyst to obtain polyorganosiloxane. The emulsifier is preferably an anionic emulsifier. Examples of the anionic emulsifier include sodium alkylbenzenesulfonate, sodium lauryl sulfate, and sodium polyoxyethylene nonylphenyl ether sulfate. These emulsifiers may be used alone or in combination of two or more. Examples of the acid catalyst include sulfonic acids such as aliphatic sulfonic acid, aliphatic-substituted benzenesulfonic acid, and aliphatic-substituted naphthalenesulfonic acid; mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid. These acid catalysts may be used alone or in combination of two or more.

[0042] The vinyl polymer constituting the shell layer may be a homopolymer or copolymer of a vinyl radical polymerizable monomer (a4). Examples of the vinyl radical polymerizable monomer (a4) include the vinyl radical polymerizable monomer (a1) exemplified above in the description of the component (A).

[0043] The component (B) is prepared from a rubber polymer (diene rubber polymer, acrylic rubber polymer, organosiloxane rubber polymer, etc.) that will form the core layer and a vinyl radical polymerizable monomer (a4) that will form the shell layer as raw materials. For example, the component (B) can be produced as a latex by adding the vinyl radical polymerizable monomer (a4) to a latex of the rubber polymer and subjecting it to a known polymerization method such as emulsion polymerization.

[0044] For ease of blending with component (C), component (B) is preferably handled as an "epoxy dispersion of component (B)" obtained by removing water and emulsifier from latex and replacing them with epoxy resin. The epoxy dispersion liquid of component (B) may be a commercially available product, such as "Kane Ace MX Series" manufactured by Kaneka Corporation. "Kane Ace MX154," an example of the "Kane Ace MX Series," is a dispersion liquid in which a polymer (about 40% by mass) having a core-shell structure in which the core layer is polybutadiene and the shell layer is a vinyl polymer is dispersed as a single particle in bisphenol A type epoxy resin (about 60% by mass).

[0045] <(C) component> The component (C) is an epoxy resin (C). Any known compound can be used as component (C), and there are no particular limitations on the molecular structure, molecular weight, etc., so long as it has at least one epoxy group in the molecule. Examples of the component (C) include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, bisphenol E type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins, and glycidyl amine type epoxy resins.

[0046] Further examples of the component (C) include prepolymers of the above-mentioned epoxy resins, copolymers of the above-mentioned epoxy resins with other polymers, such as polyether-modified epoxy resins and silicone-modified epoxy resins, and those in which a portion of the above-mentioned epoxy resins has been substituted with a reactive diluent having an epoxy group. Examples of reactive diluents include monoglycidyl compounds such as resorcinol glycidyl ether, t-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyldimethoxysilane, 1-(3-glycidoxypropyl)-1,1,3,3,3-pentamethylsiloxane, and N-glycidyl-N,N-bis[3-(trimethoxysilyl)propyl]amine; and monoalicyclic epoxy compounds such as 2-(3,4)-epoxycyclohexyl)ethyltrimethoxysilane. These reactive diluents may be used alone or in combination of two or more.

[0047] Among these, bisphenol A type epoxy resins and bisphenol F type epoxy resins are preferred as component (C) because they are liquid and easy to handle, and because they have high glass transition points and thus increase the adhesive strength of the cured product. These components (C) may be used alone or in combination of two or more.

[0048] <(D) component> The component (D) is a curing agent. Component (D) cures component (C) and is used to adjust the curability of the epoxy resin composition and the properties of the cured product. As the component (D), known compounds can be used, such as acid anhydrides, amine compounds, phenol compounds, and latent hardeners.

[0049] Specific examples of the component (D) include acid anhydrides such as phthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylhimic anhydride, methylcyclohexene dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol tristrimellitate, dodecenyl succinic anhydride, polyazelaic anhydride, and poly(ethyloctadecanedioic) anhydride;2,5(2,6)-bis(aminomethyl)bicyclo[2,2,1]heptane, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, bis(4-aminocyclohexyl)methane, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiethyldiphenylmethane, diethyltoluenediamine, diaminodiphenylsulfones such as 3,3'-diaminodiphenylsulfone (3,3'-DDS), 4,4'-diaminodiphenylsulfone (4,4'-DDS), diaminodiphenylether (DADPE), bisaniline, dimethylaniline, triethylenediamine, dimethylbenzylamine, 2,4,6-tris(dimethylaminomethyl) amine compounds such as phenol, benzyldimethylaniline, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4,4'-diaminodiphenylmethane, 2,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2'-diaminobiphenyl, 3,3'-diaminobiphenyl, 2,4-diaminophenol, 2,5-diaminophenol, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, m-xylylenediamine, 2,3-tolylenediamine, 2,4-tolylenediamine, 2,5-tolylenediamine, 2,6-tolylenediamine, 3,4-tolylenediamine, methylthiotoluenediamine, diethyltoluenediamine, and dicyandiamide; phenol compounds such as phenol novolac resin, cresol novolac resin, bisphenol A, bisphenol F, bisphenol AD, and diallylated derivatives of these bisphenols;Carbohydrazide, Oxalic Acid Dihydrazide, Malonic Acid Dihydrazide, Succinic Acid Dihydrazide, Iminodiacetic Acid Dihydrazide, Adipic Acid Dihydrazide, Pimelic Acid Dihydrazide, Suberic Acid Dihydrazide, Azelaic Acid Dihydrazide, Sebacic Acid Dihydrazide, Dodecane Dihydrazide, Hexadecane Dihydrazide, Maleic Acid Dihydrazide, Fumaric Acid Dihydrazide, Diglycolic Acid Examples of hydrazide compounds include dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4'-bisbenzenedihydrazide, 1,4-naphthoic acid dihydrazide, Amicure VDH, Amicure UDH (all trade names, manufactured by Ajinomoto Co., Inc.), and citric acid trihydrazide. Among these, from the viewpoint of improving the storage stability of the epoxy resin composition, the component (D) is preferably an amine compound or a hydrazide compound, and more preferably dicyandiamide or a hydrazide compound. These components (D) may be used alone or in combination of two or more.

[0050] <Optional ingredients> Optional components include, for example, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), 2-methylimidazole, 2-ethyl-4-methylimidazole, adducts of imidazole compounds and epoxy resins, triphenylphosphine, tetraphenylphosphine tetraphenylborate, diazabicycloundecene (DBU) and other curing accelerators; 2,6-di-t-butylphenol, 2,6-di-t-butyl-p-cresol, n-octadecyl-3-(3', 5'-di-t-butyl-4'-hydroxyphenyl)propionate, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, triethylene glycol bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], triethyl phosphite, tri(2-ethylhexyl)phospha , tridecyl phosphite, triphenyl phosphite, trisisodecyl phosphite, tristridecyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, dihexyl sulfide, dilauryl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearal-3,3'-thiodipropionate, pentaerythritol tetrakis(β-laurylthiopropionate) ) and other antioxidants; release agents such as silicone oil, natural wax, synthetic wax, and other; fillers such as glass beads, crystalline silica, fused silica, calcium silicate, alumina, calcium carbonate, and other fibers such as glass fiber, carbon fiber, alumina fiber, cellulose nanofiber, and other fibers; flame retardants such as antimony trioxide, and other halogen trapping agents such as hydrotalcite and rare earth oxides, colorants such as carbon black and red iron oxide, silane coupling agents, defoamers, rheology adjusters: pigments, dyes, and the like. These optional components may be used alone or in combination of two or more.

[0051] <Content> When the total content of the components (A), (B), (C) and (D) is taken as 100 mass %, the preferred content of each component is as follows. The content of the component (A) is preferably 1 to 50 mass%, more preferably 3 to 45 mass%, and even more preferably 5 to 40 mass%, because this allows the epoxy resin composition to have a low viscosity with good workability while further increasing the adhesive strength of the cured product. The content of the (B) component is preferably 1 to 40 mass%, more preferably 2 to 30 mass%, and even more preferably 3 to 20 mass%, because this allows the epoxy resin composition to have a low viscosity with good workability while further increasing the adhesive strength of the cured product. The content of the component (C) is preferably 40 to 95 mass %, more preferably 45 to 90 mass %, and even more preferably 50 to 85 mass %, because this allows the epoxy resin composition to have a low viscosity and good workability. The content of the (D) component is preferably 0.1 to 10 mass%, more preferably 0.5 to 9 mass%, and even more preferably 1 to 8 mass%, because this provides sufficient curability to obtain a cured product while improving the storage stability of the epoxy resin composition.

[0052] <Manufacturing method> The method for producing the epoxy resin composition is not particularly limited, and any known method can be used. For example, the components (A), (B), (C) and (D) may be mixed simultaneously with any optional components as required, or some of the components (e.g., the components (A) and (C)) may be mixed in advance, and the mixture may be mixed with the remaining components. The mixing method is not particularly limited, and a known mixer such as a planetary centrifugal mixer, a three-roll mill, or a kneader can be used.

[0053] <Action and effect> The epoxy resin composition of the present invention described above contains the above-mentioned components (A), (B), (C) and (D), and therefore can give a cured product with excellent adhesive strength. Moreover, the cured product obtained from the epoxy resin composition of the present invention has high toughness due to the action of components (A) and (B).

[0054] <Application> INDUSTRIAL APPLICABILITY The epoxy resin composition of the present invention is useful as an adhesive since it gives a cured product having excellent adhesive strength. Furthermore, the epoxy resin composition of the present invention is useful as a molding material since it gives a cured product having high toughness. The use of the epoxy resin composition of the present invention is not limited to the above. The epoxy resin composition of the present invention can also be used for other purposes, for example, for various purposes in which thermosetting resins such as epoxy resins are used. Examples of such uses include paints, coating agents, insulating materials (including printed circuit boards, electric wire coatings, etc.), sealants, etc. The adhesive and molding material containing the epoxy resin composition of the present invention will be described below.

[0055] [glue] The adhesive of the present invention contains the above-mentioned epoxy resin composition of the present invention. Examples of adhesives include adhesives for vehicles such as automobiles, adhesives for civil engineering and construction, adhesives for electronic materials, adhesives for general office use, adhesives for medical use, and adhesives for industrial use. Examples of adhesives for vehicles include hemming adhesives, weld bond adhesives, mastic adhesives, direct glazing adhesives, spot sealers, body sealers, and undercoats. Examples of adhesives for electronic materials include interlayer adhesives for multilayer substrates such as build-up substrates, die bonding agents, adhesives for semiconductors such as underfills, underfills for reinforcing BGAs, and mounting adhesives such as anisotropic conductive films (ACFs) and anisotropic conductive pastes (ACPs).

[0056] [Cured product] The cured product of the present invention is obtained by curing the above-mentioned epoxy resin composition of the present invention. The method for curing the epoxy resin composition is not particularly limited, and any known method can be used, such as a thermal curing method. When the epoxy resin composition is cured by a heat curing method, the optimal conditions vary depending on the type and amount of the component (D) contained in the epoxy resin composition, but it is preferable to cure the epoxy resin composition under heating conditions of, for example, 50 to 250°C for about 0.1 to 10 hours.

[0057] [Molding material] The molding material of the present invention contains the cured product of the above-mentioned epoxy resin composition of the present invention. Examples of molding materials include the epoxy resin composition of the present invention cured into a sheet or film; fiber reinforced plastics (FRP: Fiber Reinforced Plastics) obtained by curing a prepreg in which reinforcing fibers such as glass fibers or carbon fibers are impregnated with the epoxy resin composition of the present invention; and the epoxy resin composition of the present invention cured into a specific shape by a technique such as transfer molding or cast molding. Applications of the molding materials include, for example, aircraft, automobiles, sporting goods, windmills, electronic circuit boards, semiconductor encapsulants, and reflectors for optical semiconductors. EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In each of the following examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0059] [Measurement and evaluation method] <Measurement of molecular weight of macromonomer (a2)> The molecular weight of the macromonomer (a2) was measured using a gel permeation chromatograph (GPC apparatus) (manufactured by Tosoh Corporation, product name "HLC-8320") as follows. The macromonomer (a2) was dissolved in tetrahydrofuran (THF) so as to give a concentration of 0.2% by mass, thereby preparing a THF solution (1). 10 μL of the above THF solution (1) was injected into a GPC apparatus equipped with columns manufactured by Tosoh Corporation (TSKgel SuperHZM-M (inner diameter 4.6 mm, length 15 cm) x 1, HZM-M (inner diameter 4.6 mm, length 15 cm) x 1, HZ-2000 (inner diameter 4.6 mm, length 15 cm) x 1, TSKguardcolumn SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm) x 1), and measurements were performed under the following conditions: flow rate: 0.35 mL / min, eluent: THF containing dibutylhydroxytoluene (BHT) as a stabilizer, column temperature: 40°C, and the mass average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of standard polystyrene.

[0060] <Measurement of Molecular Weight of (Meth)acrylic Polymer (A)> The molecular weight of the (meth)acrylic polymer (A) was measured using a gel permeation chromatograph (GPC apparatus) (manufactured by Tosoh Corporation, product name "HLC-8320") as follows. The (meth)acrylic polymer (A) was dissolved in tetrahydrofuran (THF) to a concentration of 0.2% by mass to prepare a THF solution (2). 10 μL of the above THF solution (2) was injected into a GPC apparatus equipped with columns manufactured by Tosoh Corporation (2 TSKgel SuperHZM-H (inner diameter 6.0 mm, length 15 cm), 1 TSKguardcolumn SuperHZ-H (inner diameter 4.6 mm, length 3.5 cm)), and measurement was performed under the conditions of a flow rate of 0.5 mL / min, eluent: THF containing BHT as a stabilizer, and column temperature: 40° C., and the mass average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of standard polystyrene.

[0061] <Measurement of particle size and number of particles of polymer (X) having a core-shell structure> In a mixing vessel, 13.6 parts of epoxy resin containing polymer (X) having a core-shell structure obtained in Production Example 22, 3.3 parts of dicyandiamide (manufactured by Mitsubishi Chemical Corporation, product name "DICY7"), 1.6 parts of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU, manufactured by Hodogaya Chemical Co., Ltd.), and 31.4 parts of bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828") were mixed under vacuum pressure using a stirring degassing device (manufactured by Thinky Corporation, product name "Awatori Rentaro"), and then poured into a mold set to a thickness of 6 mm using a 6 mm thick polytetrafluoroethylene spacer. The mixture was heated in an oven at 120°C for 1 hour to obtain a resin cured product. The obtained cured resin was stained using osmium tetroxide (OsO4), then thin-sectioned, and the morphology was observed using a transmission electron microscope (TEM) (Hitachi, Ltd., product name "H-7600", accelerating voltage 80 kV). From the obtained TEM image, the length of the major axis of the particles of the polymer (X) having a core-shell structure was measured as the particle diameter, and the number of particles of the polymer (b1) having a core-shell structure having a particle diameter of 50 to 190 nm and the number of particles of the polymer (b2) having a core-shell structure having a particle diameter of 195 to 300 nm were counted.

[0062] <Measurement of particle size and number of particles of polymer (B-1) having a core-shell structure> In a mixing vessel, 10.2 parts of Kane Ace MX154 (manufactured by Kaneka Corporation) as an epoxy dispersion of polymer (B-1) having a core-shell structure, 3.3 parts of dicyandiamide (manufactured by Mitsubishi Chemical Corporation, product name "DICY7"), 1.6 parts of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU, manufactured by Hodogaya Chemical Co., Ltd.), and 33.8 parts of bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828") were mixed under vacuum pressure using a stirring and degassing device (manufactured by Thinky Corporation, product name "Awatori Rentaro"), and then poured into a mold set to a thickness of 6 mm using a 6 mm thick polytetrafluoroethylene spacer. The mixture was heated in an oven at 120°C for 1 hour to obtain a resin cured product. The obtained cured resin was stained using osmium tetroxide (OsO4), then thin-sectioned, and the morphology was observed using a transmission electron microscope (TEM) (Hitachi, Ltd., product name "H-7600", accelerating voltage 80 kV). From the obtained TEM image, the length of the major axis of the particles of the polymer (B-1) having a core-shell structure was measured as the particle diameter, and the number of particles of the polymer (b1) having a core-shell structure having a particle diameter of 50 to 190 nm and the number of particles of the polymer (b2) having a core-shell structure having a particle diameter of 195 to 300 nm were counted.

[0063] <Evaluation of adhesive strength> A 25 mm wide x 150 mm long x 0.5 mm thick steel plate (manufactured by Engineering Test Service Co., Ltd., product name "JISG3141SPCC-SP") was used as a gripping portion on one side of the plate from one end to 50 mm in the length direction, and the epoxy resin composition was applied to the remaining portion. Another steel plate of the same size was attached to the epoxy resin composition-applied surface, fixed so that the thickness of the epoxy resin composition layer was constant, and heated at 180°C for 30 minutes to cure the epoxy resin composition, thereby obtaining a laminate. The cured epoxy resin composition protruding from the side of the obtained laminate was scraped off, and the gripping portion of each of the two steel plates was bent at a right angle of 90° toward the outside to obtain a T-shaped test piece. Using a precision universal testing machine (Shimadzu Corporation, product name "Autograph AG-IS", load cell 1kN), the gripping portion of the obtained test piece was held above and below, and the peel strength was measured at 23°C and 200 mm / min. The average value of the load excluding the first 25 mm and the last 25 mm was taken as the T-peel strength. The T-peel strength was measured for three test pieces, and the average value was calculated to evaluate the adhesive strength. A higher T-peel strength indicates better adhesive strength.

[0064] [Dispersant] <Synthesis Example 1: Synthesis of Dispersant (1)> In a polymerization apparatus equipped with a stirrer, a cooling tube, a thermometer, and a nitrogen gas inlet tube, 900 parts of deionized water, 60 parts of 2-sulfoethyl sodium methacrylate, 10 parts of potassium methacrylate, and 12 parts of methyl methacrylate (MMA) were placed and stirred, and the temperature was raised to 50°C while replacing the inside of the polymerization apparatus with nitrogen. 0.08 parts of 2,2'-azobis(2-methylpropionamidine) dihydrochloride were added thereto as a polymerization initiator, and the temperature was further raised to 60°C. After the temperature was raised, MMA was continuously dropped at a rate of 0.24 parts / min for 75 minutes using a dropping pump. The reaction solution was kept at 60°C for 6 hours, and then cooled to room temperature to obtain a transparent aqueous solution of dispersant (1) with a solid content of 10%.

[0065] [Chain transfer agent] <Synthesis Example 2: Synthesis of Chain Transfer Agent (1)> In a synthesis apparatus equipped with a stirrer, 1.00 g of cobalt (II) acetate tetrahydrate, 1.93 g of diphenylglyoxime, and 80 mL of diethyl ether previously deoxygenated by nitrogen bubbling were placed under a nitrogen atmosphere and stirred at room temperature for 30 minutes. Next, 10 mL of boron trifluoride diethyl ether complex was added and stirred for an additional 6 hours. The mixture was filtered, the solid was washed with diethyl ether, and vacuum dried for 15 hours to obtain 2.12 g of chain transfer agent (1) as a reddish brown solid.

[0066] [Macromonomer (a2)] <Production Example 1: Production of Macromonomer (a2-1)> In a polymerization apparatus equipped with a stirrer, a cooling tube, a thermometer, and a nitrogen gas inlet tube, 145 parts of deionized water, 0.1 parts of sodium sulfate, and 0.25 parts of dispersant (1) (solid content 10%) were added and stirred to obtain a uniform aqueous solution. Next, 50 parts of MMA and 50 parts of glycidyl methacrylate (GMA) as vinyl radical polymerizable monomers (a3), 0.0040 parts of chain transfer agent (1), and 2 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name "Perocta O") as a polymerization initiator were added to obtain an aqueous suspension. Next, the inside of the polymerization apparatus was replaced with nitrogen, the temperature was raised to 80°C and the reaction was carried out for 3.5 hours, and in order to further increase the polymerization rate, the temperature was raised to 90°C and maintained for 1 hour. Thereafter, the reaction liquid was cooled to 40°C to obtain an aqueous suspension containing the macromonomer. This aqueous suspension was filtered through a filter, and the residue remaining on the filter was washed with deionized water, dehydrated, and dried at 40°C for 16 hours to obtain the macromonomer (a2-1). The molecular weight of the resulting macromonomer (a2-1) was measured, and the results are shown in Table 1.

[0067] <Production Examples 2 to 5: Production of Macromonomers (a2-2) to (a2-5)> Macromonomers (a2-2) to (a2-5) were obtained in the same manner as in Production Example 1, except that the type and amount of the vinyl radical polymerizable monomer (a3) ​​and the amounts of the chain transfer agent and polymerization initiator were changed to the values ​​shown in Table 1. The molecular weights of the resulting macromonomers (a2-2) to (a2-5) were measured, and the results are shown in Table 1.

[0068] [Table 1]

[0069] The abbreviations in Table 1 are as follows. ·MMA: Methyl methacrylate. · GMA: Glycidyl methacrylate. Chain transfer agent (1): The chain transfer agent synthesized in Synthesis Example 2. Perocta O: 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name "Perocta O").

[0070] [(Meth)acrylic polymer (A)] <Production Example 6: Production of (meth)acrylic polymer (A-1)> In a four-neck flask equipped with a stirrer, a thermometer, a cooling tube and a nitrogen gas inlet, 40 parts of methyl ethyl ketone (MEK) and 15 parts of isopropyl alcohol (IPA) were placed as initial charge solvents, and 20 parts of macromonomer (a2-1) as macromonomer (a2) were placed, and the external temperature was raised to 85°C under nitrogen gas aeration. After the external temperature reached 85°C and the internal temperature stabilized, a mixture consisting of 20 parts of MEK, 40 parts of ethyl acrylate and 40 parts of n-butyl acrylate as vinyl radical polymerizable monomers (a1), and 0.13 parts of benzoyl peroxide (manufactured by NOF Corp., trade name: "Niper BMT-K40") as a polymerization initiator was added dropwise over 4 hours. After holding for 1 hour after the end of the dropwise addition, a mixture consisting of 0.5 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corp., trade name "Perocta O") as a polymerization initiator and 10 parts of MEK was added over 1 hour. After that, after keeping for 2 hours, MEK was added so that the solid content (proportion of the monomer charge in the (monomer + solvent charge)) became 50%, and then the mixture was cooled to room temperature to obtain a (meth)acrylic polymer (A-1) solution. The molecular weight of the resulting (meth)acrylic polymer (A-1) was measured, and the results are shown in Table 2.

[0071] <Production Examples 7, 8, 16, and 17: Production of (meth)acrylic polymers (A-2), (A-3), (A-11), and (A-12)> Except for changing the type and amount of the vinyl radical polymerizable monomer (a1), the amount of the macromonomer (a2), and the type and amount of the initially charged solvent to the values ​​shown in Table 2, the same procedure as in Production Example 6 was repeated to obtain solutions of (meth)acrylic polymers (A-2), (A-3), (A-11), and (A-12). The molecular weights of the resulting (meth)acrylic polymers (A-2), (A-3), (A-11) and (A-12) were measured, and the results are shown in Table 2.

[0072] <Production Example 9: Production of (meth)acrylic polymer (A-4)> In a four-neck flask equipped with a stirrer, a thermometer, a cooling tube and a nitrogen gas inlet, 55 parts of ethyl acetate and 20 parts of macromonomer (a2-1) were placed as initial charge solvents, and the external temperature was raised to 85°C under nitrogen gas aeration. After the external temperature reached 85°C and the internal temperature stabilized, a mixture consisting of 20 parts of ethyl acetate, 80 parts of 2-ethylhexyl acrylate, and 0.13 parts of benzoyl peroxide (manufactured by NOF Corp., trade name: "Niper BMT-K40") was added dropwise over 4 hours. After holding for 1 hour after the end of the dropwise addition, a mixture consisting of 0.5 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corp., trade name "Perocta O") and 10 parts of ethyl acetate was added over 1 hour. After that, after keeping for 2 hours, ethyl acetate was added so that the solid content (ratio of the amount of monomer charged in (the amount of monomer + solvent charged)) became 50%, and then the mixture was cooled to room temperature to obtain a (meth)acrylic polymer (A-4) solution. The molecular weight of the resulting (meth)acrylic polymer (A-4) was measured, and the results are shown in Table 2.

[0073] <Production Example 10: Production of (meth)acrylic polymer (A-5)> Except for changing the type and amount of the vinyl radical polymerizable monomer (a1) to the values ​​shown in Table 2, the same procedure as in Production Example 9 was carried out to obtain a (meth)acrylic polymer (A-5) solution. The molecular weight of the resulting (meth)acrylic polymer (A-5) was measured, and the results are shown in Table 2.

[0074] <Production Example 11: (Meth)acrylic polymer (A-6)> In a four-neck flask equipped with a stirrer, a thermometer, a cooling tube and a nitrogen gas inlet, 70 parts of MEK and 50 parts of macromonomer (a2-1) were placed as initial charge solvents, and the external temperature was raised to 85°C under nitrogen gas aeration. After the external temperature reached 85°C and the internal temperature stabilized, a mixture consisting of 10 parts of MEK, 25 parts of ethyl acrylate, 25 parts of n-butyl acrylate, and 0.13 parts of benzoyl peroxide (manufactured by NOF Corp., trade name: "Niper BMT-K40") was added dropwise over 4 hours. After holding for 1 hour after the end of the dropwise addition, a mixture consisting of 0.5 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corp., trade name "Perocta O") and 10 parts of MEK was added over 1 hour. After that, after keeping for 2 hours, MEK was added so that the solid content (proportion of the monomer charge in the (monomer + solvent charge)) became 50%, and then the mixture was cooled to room temperature to obtain a (meth)acrylic polymer (A-6) solution. The molecular weight of the resulting (meth)acrylic polymer (A-6) was measured, and the results are shown in Table 2.

[0075] <Production Examples 12, 18 to 21: Production of (meth)acrylic polymers (A-7), (A-13) to (A-16)> Except for changing the type and amount of the vinyl radical polymerizable monomer (a1) and the type of the macromonomer (a2) to the values ​​shown in Table 2, the same procedure as in Production Example 11 was carried out to obtain (meth)acrylic polymer (A-7) and (A-13) to (A-16) solutions. The molecular weights of the resulting (meth)acrylic polymers (A-7) and (A-13) to (A-16) were measured, and the results are shown in Table 2.

[0076] <Production Example 13: Production of (meth)acrylic polymer (A-8)> In a four-neck flask equipped with a stirrer, a thermometer, a cooling tube and a nitrogen gas inlet, 70 parts of ethyl acetate and 50 parts of macromonomer (a2-1) were placed as initial charge solvents, and the external temperature was raised to 85°C under nitrogen gas aeration. After the external temperature reached 85°C and the internal temperature stabilized, a mixture consisting of 10 parts of ethyl acetate, 50 parts of 2-ethylhexyl acrylate and 0.13 parts of benzoyl peroxide (manufactured by NOF Corp., trade name: "Niper BMT-K40") was added dropwise over 4 hours. After holding for 1 hour after the end of the dropwise addition, a mixture consisting of 0.5 parts of 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (manufactured by NOF Corp., trade name "Perocta O") and 10 parts of ethyl acetate was added over 1 hour. After that, after keeping for 2 hours, ethyl acetate was added so that the solid content (proportion of the amount of monomer charged in (the amount of monomer + solvent charged)) became 50%, and then the mixture was cooled to room temperature to obtain a (meth)acrylic polymer (A-8) solution. The molecular weight of the resulting (meth)acrylic polymer (A-8) was measured, and the results are shown in Table 2.

[0077] <Production Examples 14 and 15: Production of (meth)acrylic polymers (A-9) and (A-10)> Except for changing the type and amount of the vinyl radical polymerizable monomer (a1) to the values ​​shown in Table 2, the same procedure as in Production Example 13 was carried out to obtain (meth)acrylic polymer (A-9) and (A-10) solutions. The molecular weights of the resulting (meth)acrylic polymers (A-9) and (A-10) were measured, and the results are shown in Table 2.

[0078] [Table 2]

[0079] The abbreviations in Table 2 are as follows. ·EA: Ethyl acrylate. · n-BA: n-Butyl acrylate. · 2-EHA: 2-Ethylhexyl acrylate. ·LA: Lauryl acrylate. a2-1 to a2-5: Macromonomers (a2) produced in Production Examples 1 to 5. ·MEK: Methyl ethyl ketone. ·IPA: Isopropyl alcohol.

[0080] [Polymers with core-shell structure] <Production Example 22: Production of epoxy resin containing polymer (X) having a core-shell structure> Component (1) in Table 3 was charged into a 70L autoclave, and when the internal temperature reached 50°C, component (2) in Table 3 was added as a redox initiator into the autoclave to initiate polymerization, and the temperature was further raised to 60°C and reacted for 7 hours. Then, components (3) and (4) in Table 3 were added dropwise over 8 hours. After the dropwise addition, the internal temperature was raised to 80°C, component (5) in Table 3 was added, and the reaction was continued for 10 hours to obtain a rubber latex. Next, 80 parts of rubber latex as resin solids were charged into a reaction vessel, and the internal temperature was raised to 70°C, and then an aqueous solution in which 0.3 parts of sodium formaldehyde sulfoxylate was dissolved in 10 parts of deionized water was added. While maintaining the internal temperature at 70°C, component (6) in Table 3 was added dropwise over 120 minutes, and the mixture was maintained for 60 minutes to polymerize, to obtain a rubber-containing polymer latex.

[0081] [Table 3]

[0082] To the obtained rubber-containing graft polymer latex, 0.25 parts of a hindered phenol-based antioxidant (manufactured by BASF Japan Ltd., product name "Irganox245") and 0.75 parts by mass of dilauryl thiodipropionate (manufactured by Mitsubishi Chemical Corporation, product name "DLTP Yoshitomi") were added as antioxidants. This was added to 270 parts by mass of deionized water containing 5 parts by mass of calcium acetate to coagulate the polymer, which was then washed with deionized water, dehydrated, and dried to obtain a polymer (X) having a core-shell structure. 70 parts of bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828") and 30 parts of polymer (X) having a core-shell structure were added to a mixing vessel and mixed using a stirring degassing device (manufactured by Thinky Corporation, product name "Awatori Rentaro"), and the resulting mixture was kneaded with a three-roll mill (manufactured by Imex Co., Ltd.) to obtain an epoxy resin containing polymer (X) having a core-shell structure.

[0083] The particle size and number of the polymer (X) having a core-shell structure were measured using the obtained epoxy resin containing the polymer (X) having a core-shell structure. The obtained TEM image is shown in Figure 1. In the obtained TEM images, the particle sizes of the polymer (X) having a core-shell structure were all within the range of 50 to 190 nm.

[0084] <Polymer having a core-shell structure (B-1)> The particle size and number of particles were measured using Kane Ace MX154, a product of Kaneka Corporation, as an epoxy dispersion of the polymer (B-1) having a core-shell structure. The resulting TEM image is shown in FIG. The polymer (B-1) having a core-shell structure in the obtained TEM image contained 360 particles of polymer (b1) having a core-shell structure with a particle diameter of 50 to 190 nm and 60 particles of polymer (b2) having a core-shell structure with a particle diameter of 195 to 300 nm, and the b1 / b2 ratio was 6. In addition, no polymer (b3) having a core-shell structure was contained.

[0085] [Example 1] 100 parts of the (meth)acrylic polymer (A-1) solution obtained in Production Example 6 was mixed with 50 parts of a bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828"), and MEK and IPA were distilled off under reduced pressure using a vacuum dryer, thereby obtaining a (meth)acrylic polymer-containing epoxy resin containing 50 parts of the (meth)acrylic polymer (A-1). A mixing vessel was charged with 20 parts of a (meth)acrylic polymer-containing epoxy resin as components (A) and (C) (breakdown: 10 parts of (meth)acrylic polymer (A-1) and 10 parts of jER828), 35.2 parts of Kane Ace MX154 (trade name) manufactured by Kaneka Corporation as components (B) and (C) (breakdown: 14 parts of polymer (B-1) having a core-shell structure and 21.2 parts of bisphenol A type epoxy resin), 4.8 parts of dicyandiamide (manufactured by Mitsubishi Chemical Corporation, trade name "DICY7") as component (D), and 3-(3,4-dichlorophenyl)-2-propanediol as a curing accelerator. An epoxy resin composition was prepared by adding 0.9 parts of (phenyl)-1,1-dimethylurea (manufactured by Hodogaya Chemical Co., Ltd., product name "DCMU"), 18 parts of calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., product name "Whiten B") as a filler, and 3.5 parts of glass beads (manufactured by Potters Ballotini Co., Ltd., product name "J-100"), and 40 parts of bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828") as component (C). The mixture was mixed using a stirring degassing apparatus (manufactured by Thinky Corporation, product name "Awatori Rentaro"). The adhesive strength of the obtained epoxy resin composition was evaluated, and the results are shown in Table 4.

[0086] [Examples 2 to 25, Comparative Examples 1 to 8] Epoxy resin compositions were prepared in the same manner as in Example 1, except that the type and amount of component (A), the type and amount of polymer having a core-shell structure, and the amount of component (C) were changed to the values ​​shown in Tables 4 to 6. The adhesive strength of the obtained epoxy resin composition was evaluated, and the results are shown in Tables 4 to 6.

[0087] [Table 4]

[0088] [Table 5]

[0089] [Table 6]

[0090] The abbreviations in Table 4 are as follows. A-1 to A-16: (meth)acrylic polymers (A) produced in Production Examples 6 to 21. B-1: Polymer (B) having a core-shell structure, included in the product name "Kane Ace MX154" manufactured by Kaneka Corporation. · jER828: Bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER828"). Bisphenol A epoxy: Bisphenol A type epoxy resin contained in the product name "Kane Ace MX154" manufactured by Kaneka Corporation. DICY: Dicyandiamide (manufactured by Mitsubishi Chemical Corporation, product name "DICY7"). DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea (manufactured by Hodogaya Chemical Industry Co., Ltd., trade name "DCMU"). · Whiten B: Calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., product name "Whiten B"). J-100: Glass beads (manufactured by Potters Barotini Co., Ltd., product name "J-100"). Polymer (X) having a core-shell structure: Polymer (X) having a core-shell structure obtained in Production Example 22.

[0091] As is clear from Tables 4 to 6, the cured products of the epoxy resin compositions obtained in each Example had excellent adhesive strength. On the other hand, the cured products of the epoxy resin compositions obtained in the respective Comparative Examples were poor in adhesive strength. [Industrial Applicability]

[0092] Since the epoxy resin composition of the present invention can give a cured product having excellent adhesive strength, the epoxy resin composition of the present invention is useful as an adhesive, for example, an adhesive for vehicles such as automobiles, an adhesive for civil engineering and construction, an adhesive for electronic materials, an adhesive for general office use, an adhesive for medical use, an adhesive for industrial use, and the like.

Claims

1. An epoxy resin composition comprising a (meth)acrylic polymer (A), a polymer having a core-shell structure (B), an epoxy resin (C), and a curing agent (D), the (meth)acrylic polymer (A) has a structural unit derived from a vinyl radically polymerizable monomer (a1) and a structural unit derived from a macromonomer (a2), the core-shell structure-having polymer (B) contains a core-shell structure-having polymer (b1) having a particle diameter of 50 to 190 nm and a core-shell structure-having polymer (b2) having a particle diameter of 195 to 300 nm; the number of particles of the polymer (b1) having a core-shell structure and the number of particles of the polymer (b2) having a core-shell structure satisfy the following formula (i): 0.05≦(number of particles of polymer (b1) having a core-shell structure / number of particles of polymer (b2) having a core-shell structure)≦20 (i)

2. a core layer of the polymer (B) having a core-shell structure is one or more selected from the group consisting of a diene-based rubber polymer, an acrylic-based rubber polymer, and an organosiloxane-based rubber polymer, and a shell layer of the polymer (B) having a core-shell structure is a vinyl-based polymer; The epoxy resin composition according to claim 1.

3. 3. The epoxy resin composition according to claim 1, wherein the macromonomer (a2) has a structural unit derived from a vinyl radically polymerizable monomer (a3).

4. The epoxy resin composition according to claim 3 , wherein the macromonomer (a2) has a structure represented by the following general formula (1): 【Chemistry 1】 (In formula (1), X 1 ~X n-1 are each independently a hydrogen atom, a methyl group, or CH 2 OH and Y 1 ~Y n each independently represents X bonded to a vinyl group of the vinyl radical polymerizable monomer (a3); 1 ~X n-1 Z is a terminal group, and n is an integer from 2 to 10,000.

5. The epoxy resin composition according to claim 3 or 4, wherein the vinyl radical polymerizable monomer (a3) ​​contains a (meth)acrylate having a cyclic ether group.

6. An adhesive comprising the epoxy resin composition according to any one of claims 1 to 5.

7. A cured product of the epoxy resin composition according to any one of claims 1 to 5.

8. A molding material comprising the cured product according to claim 7.

Citation Information

Patent Citations

  • Epoxy resin composition and structural adhesive

    JP2010059388A

  • Curable resin composition containing polymer fine particles

    JP2015078280A

  • Macromonomer copolymer and epoxy resin composition including the same

    JP2020012092A

  • Epoxy resin composition

    JP2020122086A

  • Macromonomer copolymer, epoxy resin composition, adhesive, molding material and cured product

    WO2019049951A1